Injuries and Health Problems in Football : What Everyone Should Know - van Dijk, C. Niek; Neyret, Philippe; Cohen, Moises; Della Villa, Stefano; Pereira, Helder; Oliveira, J. Miguel (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book offers a comprehensive overview of current knowledge on the health problems and injuries associated with football and their clinical management. After an opening section on technical aspects and fundamental principles, all areas of football traumatology are addressed. The coverage includes muscle, tendon, and stress injuries of the lower limbs and injuries to the ankle and foot, knee, hip and groin, spine and head, and upper limbs. An individual section is also devoted to the most significant heart and other health conditions that may be encountered in players of all ages and standards. Follow-up, rehabilitation, and return to activity are discussed, and the role of performance enhancement strategies is carefully examined, with description of nutritional guidelines and the evidence on use of dietary supplements. A concluding section highlights the potential of the next generation of biologics to improve the regeneration and biofunctionality of damaged tissues. This book is written by world-renowned experts and has been produced in cooperation with ISAKOS. It will serve as a reference in the field of orthopaedics.
Keywords: Medicine.; Orthopedics.; Rehabilitation.; Sports medicine.; Traumatology.; elektronické knihy; electronic books